Muscle loss in cancer cachexia: what is the basis for nutritional support? - Faiad, Jaline; Andrade, Márcia Fábia; de Castro, Gabriela; de Resende, Joyce; Coêlho, Marina; Aquino, Giovana; Seelaender, Marilia (Frontiers in Pharmacology, 2025)
Cancer cachexia (CC) is characterized by significant skeletal muscle wasting, and contributes to diminished quality of life, while being associated with poorer response to treatment and with reduced survival. Chronic inflammation plays a central role in driving CC progression, within a complex interplay favoring catabolism. Although cachexia cannot be fully reversed by conventional nutritional support, nutritional intervention shows promise for the prevention and treatment of the syndrome. Of special interest are nutrients with antioxidant and anti-inflammatory potential and those that activate pathways involved in muscle mass synthesis and/or in the inhibition of muscle wasting. Extensive research has been carried out on novel nutritional supplements’ power to mitigate CC impact, while the mechanisms through which some nutrients or bioactive compounds exert beneficial effects on muscle mass are still not totally clear. Here, we discuss the most studied supplements and nutritional strategies for dealing with muscle loss in CC.